The ABCs for Smart Regulations : Education and the Quality of Business Regulations - Novik, Nadia (World Bank, Washington, DC, 2020)
Despite a wide range of research discussing the connection between education and entrepreneurship, one aspect remains untouched which is the association between education and the business regulatory framework. The authors conduct the analysis using various metrics of education to account for both its length and quality. The purpose of this paper is to fill this gap and investigate a relationship between education and the quality of the legal framework that regulates local small and medium firms.